2013
DOI: 10.1007/s00256-013-1790-5
|View full text |Cite
|
Sign up to set email alerts
|

MRI performed on dedicated knee coils is inaccurate for the measurement of tibial tubercle trochlear groove distance

Abstract: This study has identified a highly significant difference in TTD measurement when knees are scanned in a dedicated knee coil with the knee partially flexed, compared with an MR body coil. It is critical for surgeons and radiologists managing patello-femoral instability to appreciate this profound difference. TTD measurement taken from knees scanned in dedicated knee coils may lead to patients being falsely re-assured or erroneously denied surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 18 publications
1
29
2
6
Order By: Relevance
“…37 For instance, TTTG values were acquired at various flexion and extension degrees of the knee; however, it was shown that the TTTG distance increases significantly in the end-stage extension of the knee. 37,40,41 The mean TTTG values on MR images were 15.1 AE 3.2 mm at full extension, 10.0 AE 3.5 mm at 15 degrees flexion, and 8.1 AE 3.4 mm at 30 degrees flexion in a well-balanced study cohort of asymptomatic volunteers. 37 Using the MR body coil with the knee fully extended caused significantly higher TTTG values compared with MR examinations with a dedicated knee coil where the knee is slightly flexed.…”
Section: Tuberosity To the Trochlear Groove Distancementioning
confidence: 84%
See 1 more Smart Citation
“…37 For instance, TTTG values were acquired at various flexion and extension degrees of the knee; however, it was shown that the TTTG distance increases significantly in the end-stage extension of the knee. 37,40,41 The mean TTTG values on MR images were 15.1 AE 3.2 mm at full extension, 10.0 AE 3.5 mm at 15 degrees flexion, and 8.1 AE 3.4 mm at 30 degrees flexion in a well-balanced study cohort of asymptomatic volunteers. 37 Using the MR body coil with the knee fully extended caused significantly higher TTTG values compared with MR examinations with a dedicated knee coil where the knee is slightly flexed.…”
Section: Tuberosity To the Trochlear Groove Distancementioning
confidence: 84%
“…37 Using the MR body coil with the knee fully extended caused significantly higher TTTG values compared with MR examinations with a dedicated knee coil where the knee is slightly flexed. 41 In addition, the dedicated knee coil often causes a slight varus alignment of the lower limb, which also explains in part the lower TTTG distances. 39 As a consequence, the comparability of reported TTTG distance values obtained on radiographs, CT, and MRI at various flexion angles and varus alignment of the knee is limited.…”
Section: Tuberosity To the Trochlear Groove Distancementioning
confidence: 99%
“…7,16 Decreased tibial external rotation for MRI scans likely contributes to up to 4 mm smaller TT-TG distance values noted for MRI scans than CT scans. [6][7][8][9] Knee coils used for MRI scans induce knee flexion, 6,17 thereby reducing tibial external rotation associated with terminal knee extension. 18 MRI knee coils also induce $5 degrees of knee varus, further decreasing TT-TG distance.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some clinical factors that may affect the reliability of these measurement parameters, such as the knee flexion angle and quadriceps action [913]. In clinical practice, the knee is usually flexed to some degree due to the MRI coil shape, the knee position in the coil, and differences in operator habits [12]. Between conventional MRI scans, it is hard to set a uniform examination position of the knee even for the same individual.…”
Section: Introductionmentioning
confidence: 99%